The Economic Impact of Financial Integration: A Case of Chengdu-Chongqing Economic Circle - Qin, Dingyi; Thepmongkol, Athakrit (Thailand and The World Economy, 2025)
To explore the relationship between financial integration and economic growth in the 16 cities within China’s Chengdu-Chongqing Economic Circle (CCEC) from 2010 to 2019, this paper utilizes the Principal Component Analysis (PCA) to identify the degree of financial agglomeration, the Wilson Model (WM) to compute the financial radiation radius, and the Spatial Durbin Model (SDM) to conduct spatial association analysis. Results show a positive U-shaped relationship and spatial association between financial integration and economic growth. At a lower level of financial integration, it appears to hinder the economic growth of both the local and neighbouring areas, while at a higher level, it can promote regional economic growth.